Understanding orthodontists' decision making in relation to innovations from encounter to implementation: A qualitative study - Papakostopoulou, Margarita; Kučera, Josef; Tycová, Hana (American journal of orthodontics and dentofacial orthopedics, 2022)
INTRODUCTION: High-quality scientific and technological advancements are necessary if quality improvement is to be achieved in orthodontic treatment. However, suboptimal research uptake in clinical practice and innovation adoption patterns that are not consistent with scientific evidence suggest that a better understanding of the adoption behavior of clinicians is needed. This research aimed to explore the factors that influence orthodontists to adopt innovations into practice. METHODS: This was a qualitative study in which 9 semistructured in-depth interviews were conducted with orthodontists and third-year orthodontic residents. The interviews were digitally recorded, and field notes were taken. Data were professionally transcribed verbatim and deidentified. Thematic analysis was used to inductively generate codes and subsequent themes. This study was reported according to the consolidated criteria for reporting qualitative studies checklist. RESULTS: Six main themes emerged as facilitators or barriers to adoption. In addition, a sequence of events that took place from knowledge encounter through to implementation was described. Factors influencing adoption included: the perceived state of one's current practice; features of the encounter; attributes of the innovation; clinician's personality traits; practice management; and external influences relating to the professional community, patients, and marketing pressures. CONCLUSIONS: The study provides an insight into what orthodontists consider in their decisions to adopt new knowledge into clinical practice. The findings can help clinicians navigate decision making around innovation adoption by increasing awareness of the factors that influence this process to ensure that switching practice leads to quality improvement.
Keywords: Qualitative Research; Humans; rozhodování; kvalitativní výzkum; Decision Making; ortodontisté; Orthodontists; lidé